Manifestations of the Epidemic Process of Measles and Rubella at the Present Stage - A. A. Pozdnyakov; O. P. Chernyavskaya (Эпидемиология и вакцинопрофилактика)
Relevance. Measles and rubella have been known to humanity for centuries. These two infections have a number of similarities. However, despite all the similarities and a single elimination program, it is not possible to achieve the same results by the level of the incidence of these infections. Goal. Identify common features and differences in the manifestations of the epidemic process of measles and rubella at the present stage and formulate a hypothesis on their explanation.Materials and methods. Methods of retrospective epidemiological analysis of morbidity were used: Evaluation of the statistical significance of the differences in indicators with the Student’s test. To compare the rate of decrease in the incidence of measles and rubella their exponential approximations using the method of least squares were used. To process the research data, the Microsoft Excel program was used.Results. In the pre-vaccination period, the incidence of measles was 4.6 times higher than rubella. For major infections in this period characterized by a pronounced cyclic morbidity, while the intervals between cyclical rises for measles are shorter, and the amplitude of cycles is higher. As the population was vaccinated, the incidence of these infections decreased, while the rate of decline in the incidence of rubella was higher than that of measles. Also, a faster decrease in morbidity and smoothing of the cyclicity, a transition to older age groups, a gradual exit from the incidence of younger age groups confirm that the rubella has a contact number less then measles.Conclusion. The current level of population immunity is sufficient to eliminate rubella in a relatively short time. For measles, which has greater contagiousness and a contact number, and is more demanding for population immunity, this level is not enough. As a consequence, rubella shows better «manageability» in immunization than measles.